Heavy metal accumulation in two synanthropic avian species in Sri Lanka - Fernando, W. B. P. S.; Perera, S. P. P. M.; Vithanarachchi, R. M.; Wijesekera, R. D; Wijesinghe, M.R. (My University, 2020)
We assessed the levels of Pb, Cd, and Mn in contour feathers of the feral pigeon (Columba livia) and house crow (Corvus splendens) obtained from five urban/suburban locations across Sri Lanka, using the AAS following wet digestion. Our key objectives were to compare accumulation levels in the two avian species with different foraging habits and living in common locations, and to establish baseline information on the presence of these metals in multiple locations in Sri Lanka with varying levels of urbanization. Owing to reservations that have been expressed by previous workers regarding the use of feathers for assessing heavy metal pollution, we first tested the efficacy of contour feathers by using our data for comparing the coefficients of variation in metal levels within and between locations. This showed that in over 95% of the cases, variations within locations were lower than between locations, indicating that freshly shed contour feathers that were used in the present study were reliable indicators of the status of bioaccumulation of the heavy metals in the environment. In interspecific comparisons, other than in the two suburban locations, Pb was present at much higher levels in the house crow than in the feral pigeon, whereas accumulation patterns with respect to Cd and Mn were inconsistent, suggesting that granivores may not, in all situations, accumulate lower levels than scavengers in the same environment. Owing to such interspecific variations in the patterns of accumulation of different heavy metals, the selection of a single species for assessing levels of pollution from heavy metals may not be prudent. Pb and Cd levels in both species were strongly and positively associated with human population density. The levels of Pb and Cd were highest in Colombo (commercial capital). In Colombo and Kalutara, the recorded levels in the house crow exceeded the thresholds that have the potential to inflict adverse impacts on avian species.
Keywords: Contour feathers . Granivore . Monitoring . Pollution . Scavenger